Agronomic performance of runner peanut genotypes, aiming for early harvest - Martins, Kennedy Brunno de Brito (2020)
1 Â  Early runner type peanut genotypes are crucial for growing peanuts in sugarcane renewal areas. The test was installed in the experimental area of Embrapa Arroz e Feijão in Santo Antônio de Goiás-GO. The design used was in randomized blocks, containing four replications. The treatments consisted of seven strains (18-2173 OL, 18-2250 OL, 18-2133 OL, 18-2101 OL, 18-2266 OL, 17-1253 OL and 18-2094 OL) and one cultivar (BRS 423 OL). The useful area of each plot was 5.4 m2, consisting of two lines three meters long, with a spacing of 0.90 m. The plants were inverted at 118 days after emergence (DAE). Percentage of mature grains, severity of black spot, mass of 100 grains and yield were evaluated, observing significant difference for all variables. All strains showed grain maturity above 70%. The lowest grades of black spot severity were obtained from genotypes 18-2173 OL, 18-2094 OL, BRS 423 OL, 18-2133 OL, 18-2266 OL, 18-2250 OL and 17-1253 OL. The genotypes 18-2133 OL and 18-2094 OL showed yield potential above 7,400 kg.ha-1, when harvested before 120 DAE.